Papilla preservation and minimally invasive surgery for the treatment of peri‐implant osseous defects. Clinical and radiographic outcomes of a 5‐year retrospective study. Issue 11 (28th August 2021) - Cortellini, Pierpaolo; Cortellini, Simone; Bonaccini, Daniele; Tonetti, Maurizio S.
Abstract: Objectives: Evaluate in a case series the clinical applicability of a regenerative approach for treatment of peri‐implant lesions based on papilla preservation flaps (PPF) and minimally invasive surgery (MIST). Material and methods: Twenty‐one deep peri‐implant defects in 21 patients were surgically accessed applying PPF and MIST. The exposed implant surface was decontaminated with the sequential application of mechanical devices and chemical agents. Bone substitutes alone or in combination with a collagen barrier were applied, according to the anatomy of the peri‐implant lesion. Clinical and radiographic measurements were collected at baseline, post‐surgery, 1 and 5 years. Results: Primary wound closure was obtained in 100% of the sites and maintained in 90% of the sites at 1 week. Bleeding on probing (BOP) was reduced from 100% at baseline to 28.6% at 1 year and to 42.8% at 5 years. The 1‐year pocket reduction was 3.9 ± 1 mm. Residual probing depths (PD) were 4.1 ± 0.9 mm. PD remained stable up to 5 years. The radiographic bone gain was 2.5 ± 1.2 mm (mesial) and 2.5 ± 1.1 (distal) at 1‐year and 2.3 ± 1.3 mm (mesial) and 2.6 ± 1.4 mm (distal) at 5 years. The radiographic resolution of the defect was 70.4% ± 19% (mesial) and 70.2% ± 22% (distal) at 1 year and 64.2% ± 21% (mesial) and 67.7% ± 21% (distal) at 5 years. All implants survived up to 5 years. A composite outcome of disease resolution shows consistent 1‐year clinical improvements at all the treated sites and substantial 5‐year stability. Conclusions: PPF and MIST can be successfully applied for the regenerative treatment of peri‐implant defects.